PP084 Diabetic Macular Edema: A Comparison Between Treatment Options. (2017) - Ferrario, Lucrezia; Foglia, Emanuela; Bandello, Francesco; Ferri, Camilla; Figini, Innocente; Franzin, Michela; Gambaro, Gianpiera; Introini, Ugo; Medaglia, Massimo; Staurenghi, Giovanni; Tadini, Patrizia; Zuppini, Teresa; et al.
Abstract : INTRODUCTION: Health Technology Assessment (HTA) aims at providing decision makers with relevant data, matching different perspectives, with an evidence-based approach. The most common framework used is the European Network for Health Technology Assessment (EUnetHTA) Core Model (1): HTA may be further supported by a Multi-Criteria Decision Analysis (MCDA) (2, 3), leading to a final quantitative synthesis, facilitating the appraisal phase. This project presents a multi-dimensional comparison of the technologies available for the treatment of diabetic macular edema (Ranibizumab, Aflibercept, Dexamethasone implant and off-label Bevacizumab), comparing three Italian Regions: Lombardy, Liguria and Veneto. METHODS: The nine EUnetHTA dimensions were first prioritized by seventeen multidisciplinary evaluators. Thereafter a further nine professionals attributed a 3-level rating score (from "1" not performant, to "3" most performant) to each dimension and sub-dimension, after carefully assessing the three HTA reports. In conclusion, the investigation of statistically significant differences between the attributed scores of the evaluators was conducted, using a multi-variate analysis. RESULTS: No statistically significant differences were reported in the prioritization of each dimension, except for the equity (more important in Liguria and in Lombardy) and the economic financial dimensions (more relevant in Veneto and in Lombardy). Notwithstanding the evaluators' different professional titles, job roles, center size, and various Regional contexts, they attributed similar scores to the HTA dimensions during the appraisal phase (even though conducted in different years, in 2015 and 2016). This finding demonstrates the robustness of both the evaluations and the final MCDA results: i) no statistically inter-regional significant differences emerged regarding Ranibizumab and Aflibercept (p-value >.05); ii) no statistically significant inter-regional differences emerged regarding Dexamethasone, except for the assessments in the clinical dimensions (p-value = .026), since in Lombardy Region the evaluation was carried out earlier in the technology's life-cycle. CONCLUSIONS: Dexamethasone was consistently attributed a higher total score, considering the final normalised weight derived from the MCDA approach (p-value =.001).